Optimization of Cooking Processes for Rice Varieties (Oryza Sativa Linne) Produced in Benin - EKPO, K.JUSTIN; DOSSOU, JOSEPH (My University, 2023)
This study evaluated the effect of rice-to-water ratio (1; 1.5; 2; 2.5, and 3) during cooking and cooking time (10, 15, 20, and 25 min) on the textural parameters of WAB32–46, BASMATI370, NERICA4, WITA10 and C74, local rice varieties. The physicochemical and rheological characteristics of the local rice varieties were compared and their relationship with the textural parameters was determined. The firmness decreased (p < 0.001) when the rice-to-water ratio and the cooking time increased while the stickiness increased (p < 0.001) with the cooking time. The rice to water ratio and cooking time rendered the texture pasty. To obtain a good texture, the NERICA4 and BASMATI370 varieties must be cooked with cooking ratios of 2 for 20 min, WITA10, and C74 of 2 for 25 min, and the WAB32–46 variety of 1.5 for 20 min.
Keywords: Cooked rice texture; cooking time; rice to water ratio